The Perceptions on Sustainable Real Estate; A Case Study of Sri Lanka (Session 3D) - Edirisinghe, J. (Department of Property, The University of Auckland Business School, 2018)
Attached

The real estate investment in industry finds the centre of economic and social changes in any country. Similarly it plays a key role in the economy of Sri Lanka. Virtually every aspect of real estate development and operation has significant environmental consequences: from the location of the site on which structures are built, to the materials required to construct buildings and other structures (imbedded energy), and then the energy required to operate them. However its impacts vary significantly by region, depending on local climate and building technologies, among other factors. As per (Hostetler and Knowles, 2010) environmental attributes in relation to real estate development are; Open space, Trees and conserved natural areas, Road network, Wetland conservation, Lighting, Landscaping, Storm water, treatment and Resident engaging. Sri Lanka being a small island country land resources are of vital importance. Along with the other issues like limited environmental resources (timber, sand, cement), pollution the country has to search options to promote sustainable real estate. It is observed that due consideration is not given for environmental aspects in real estate development especially in urban areas of Sri Lanka. Therefore the objective of this study is to measure the environmental concern of professionals, practitioners and academics who are engaged in the activities related to real estate sector in the country. Revised New Ecological Paradigm (NEP) Scale designed by Dunlap et al. (2000) to identify the views of environmental aspects of the people was used to measure the perceptions on fifteen environmental attributes. The survey instrument was adopted and randomly selected 50 groups of respondents covering the above categories were interviewed.
Keywords: Sustainable real estate; environmental attributes; new ecological paradigm